2015
DOI: 10.1007/s00424-015-1714-4
|View full text |Cite
|
Sign up to set email alerts
|

Furosemide stimulation of parathormone in humans: role of the calcium-sensing receptor and the renin-angiotensin system

Abstract: Interactions between sodium and calcium regulating systems are poorly characterized but clinically important. Parathyroid hormone (PTH) levels are increased shortly after furosemide treatment by an unknown mechanism and this effect is blunted by the previous administration of a calcimimetic in animal studies. Here, we explored further the possible underlying mechanisms of this observation in a randomized cross-over placebo-controlled study performed in 18 human males. Volunteers took either cinacalcet (60mg) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…(30) However, a recent study suggests that loop diuretics may also be capable of directly stimulating PTH secretion, independent from calciuric effects, via loop diuretic-responsive NKCC1 receptors in parathyroid tissue. (31) Our observation of higher PTH levels with loop diuretics is echoed by studies in cohorts with chronic kidney disease who have higher PTH levels (16) and more recently in a cohort without kidney disease. (32) Thiazides decrease calciuria (potentially inducing positive calcium balance) and have been shown to increase bone density and are associated with a lower risk for fracture.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…(30) However, a recent study suggests that loop diuretics may also be capable of directly stimulating PTH secretion, independent from calciuric effects, via loop diuretic-responsive NKCC1 receptors in parathyroid tissue. (31) Our observation of higher PTH levels with loop diuretics is echoed by studies in cohorts with chronic kidney disease who have higher PTH levels (16) and more recently in a cohort without kidney disease. (32) Thiazides decrease calciuria (potentially inducing positive calcium balance) and have been shown to increase bone density and are associated with a lower risk for fracture.…”
Section: Discussionmentioning
confidence: 94%
“…Recent studies have shown that dihydropyridine L-type calcium channels, loop-diuretic-responsive NKCC1 receptors, and angiotensin type 1 and mineralocorticoid receptors are all present in parathyroid tissue. (19,31,36) …”
Section: Discussionmentioning
confidence: 99%
“…The persistence of increased parathormone level can be caused by vitamin D insuffi ciency as well. The injection of furosemid stimulates PTH secretion in healthy adults (Muller, 2015). The measurement of peroperative intact parathormone levels should be performed during miniinvasive approaches on parathyroid glands (Joliat et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In the CRIC study [3] , this difference was ascribed to the wellknown differences between TTLD and LD regarding calcium excretion [20] . However, a recent study has shown that acute administration of Furo to healthy individuals promoted an increase of PTH levels in the absence of any detectable electrolyte changes [21] , perhaps as a result of a direct effect on the Na-K-2Cl cotransporter expressed at the parathyroid gland [22] . A similar dissociation between serum calcium and PTH secretion in human subjects was observed when the administration of Furo lasted for several days [20] .…”
Section: Discussionmentioning
confidence: 99%